Second‐Harmonic and Terahertz Generation in a Prussian‐Blue Analogue. Issue 3 (5th December 2017) - Ould‐Hamouda, Amine; Iazzolino, Antonio; Tokoro, Hiroko; Ohkoshi, Shin‐Ichi; Freysz, Eric
Abstract : Second‐harmonic and terahertz generation is performed in the Rb0.94 Mn[Fe(CN)6 ]0.98 · 0.3H2 O Prussian‐blue analogue. Second‐harmonic generation experiments are carried out between 1100 and 1700 nm and within the hysteresis loop of this compound. In the low‐ and high‐temperature phases, our measurements indicate that the effective second‐order nonlinear component χ (2) of this material is small, compared with α‐quartz. However, in the high‐temperature phase and close to 1100 nm, its χ (2) is enhanced by more than one order of magnitude. Terahertz generation indicates that in this frequency range, the effective χ (2) of this compound is high and comparable with that of ZnTe. Finally, we demonstrate that within the thermal hysteresis loop of this Prussian‐blue analogue, one can modulate the χ (2) by photoswitching it from the low‐temperature to the high‐temperature phase. Abstract : We report on second‐harmonic and THz generation in the low‐ and high‐temperature phases of a Rb0.94 Mn[Fe(CN)6 ]0.98 · 0.3H2 O Prussian‐blue analogue. The evolution of the second‐order nonlinear properties of this material in the optical and THz frequency ranges versus its crystalline structure and the excitation wavelength is investigated.